Die Rechtsnachfolge in Bergbauberechtigungen und Betriebsplanzulassungen nach dem Bundesberggesetz Zugleich eine exemplarische Untersuchung der Rechtsnachfolge in umweltrechtliche Anlagen- und Produktzulassungen - Theil, Kerstin (Universitätsverlag Göttingen, 2019)
The thesis deals with the question of legal succession in public law approvals with a particular focus on the legal situation in mining law. A comparison with legal succession in different approvals in the field of environmental law provides possible solutions and at the same time highlights the necessity for an amendment of the existing provisions on legal succession in the Federal Mining Act.